The pursuit of HR outsourcing in an emerging economy: The effects of HRM strategy on HR labour costs - Abdul-Halim, H.; Che-Ha, N.; Geare, A.; Ramayah, T. (Wiley, 2016)
The study examines the relationships among six types of HRM strategies with three categories of outsourcing HR activities to reduce HR labour costs. The data were gathered from a survey questionnaire of 232 manufacturing organizations of which 113 organizations engaged with HR outsourcing. We found that no organization outsourced transformational HR functions and that organizations that espouse cost efficiency, commitment, and conventional HRM strategies tend to outsource traditional HR functions, whereas quality conscious and commitment HRM strategies tend to outsource transactional HR functions. Transactional and traditional HR functions show a significant relationship with a reduction in HR labour costs.